2020
DOI: 10.1093/mnras/staa3360
|View full text |Cite
|
Sign up to set email alerts
|

First Light And Reionization Epoch Simulations (FLARES) – I. Environmental dependence of high-redshift galaxy evolution

Abstract: We introduce the First Light And Reionisation Epoch Simulations (Flares), a suite of zoom simulations using the Eagle model. We resimulate a range of overdensities during the Epoch of Reionisation (EoR) in order to build composite distribution functions, as well as explore the environmental dependence of galaxy formation and evolution during this critical period of galaxy assembly. The regions are selected from a large (3.2 cGpc)3 parent volume, based on their overdensity within a sphere of radius 14 h−1 cMpc.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 145 publications
8
95
1
Order By: Relevance
“…There is also a similar trend at = 10, but is harder to draw conclusions from, since the Oesch et al ( 2018) data contains only 5 galaxies. Some of this tension can be −8 attributed to the slightly lower normalisation (∼ 0.3 dex) of the SFR function of the E reference volume or F at intermediate SFR (1 < SFR < 10 M yr −1 ) as noted for high-redshift galaxies in Katsianis et al (2017); Lovell et al (2021a, also see Furlong et al 2015) when compared to observed values. Vijayan et al (2021) also showed that the unobscured SFR density of F galaxies at ∈ [5, 7] showed slightly lower normalisation (∼ 0.2 dex) in comparison with the unobscured value from Bouwens et al (2020), even though the dust model was explicitly calibrated to match the UV LF, indicating that either the star formation rates are generally lower in the simulation, or the chemical enrichment rate (and thus the derived dust content) is higher, giving rise to higher attenuation than expected in these model galaxies.…”
Section: Luminosity Functionsmentioning
confidence: 85%
See 2 more Smart Citations
“…There is also a similar trend at = 10, but is harder to draw conclusions from, since the Oesch et al ( 2018) data contains only 5 galaxies. Some of this tension can be −8 attributed to the slightly lower normalisation (∼ 0.3 dex) of the SFR function of the E reference volume or F at intermediate SFR (1 < SFR < 10 M yr −1 ) as noted for high-redshift galaxies in Katsianis et al (2017); Lovell et al (2021a, also see Furlong et al 2015) when compared to observed values. Vijayan et al (2021) also showed that the unobscured SFR density of F galaxies at ∈ [5, 7] showed slightly lower normalisation (∼ 0.2 dex) in comparison with the unobscured value from Bouwens et al (2020), even though the dust model was explicitly calibrated to match the UV LF, indicating that either the star formation rates are generally lower in the simulation, or the chemical enrichment rate (and thus the derived dust content) is higher, giving rise to higher attenuation than expected in these model galaxies.…”
Section: Luminosity Functionsmentioning
confidence: 85%
“…This relation can also be used to understand the increasing dust temperatures with redshift (explicit redshift evolution is shown in Figure 10). Lovell et al (2021a) has already shown that there is a systematic increase in the normalisation of the sSFR of the F galaxies at constant stellar mass. This would imply that the redshift dependence of the dust temperature can be attributed to the increasing sSFR.…”
Section: T Peakmentioning
confidence: 86%
See 1 more Smart Citation
“…One means of circumventing this limitation is to use multiple zoom simulations of differing environments, and weight the relative abundance of each simulation based on its relative total matter overdensity. This technique was first demonstrated with the GIMIC simulations (Crain et al 2009), and recently used in the Flares simulations to make predictions for the abundance of galaxies during the epoch of reionisation (Lovell et al 2021;Vijayan et al 2021). Another drawback is that zooms cannot be used to self-consistently predict aspects of the large scale structure, such as the clustering of galaxies, since they are by construction non-representative, small volume regions of the Universe.…”
Section: Introductionmentioning
confidence: 99%
“…This will allow for the construction of extremely large lightcones (as demonstrated in Hearin et al 2020, using their empirical modelling plus simulationcalibrated approach), necessary for making predictions for wide field surveys from the upcoming Roman and Euclid space-based observatories(Potter et al 2017). To this end, in future work we will explore predictions during the epoch of reionisation, where we will leverage the Flares simulations(Lovell et al 2021). A unique aspect of Flares is that it consists of resimulations of a range of overdensities, providing training data in extreme over-and under -dense environments, which may aid predictions of galaxy properties across all environments.…”
mentioning
confidence: 99%